2021
DOI: 10.4102/hsag.v26i0.1462
|View full text |Cite
|
Sign up to set email alerts
|

The lived experiences of men who have sex with men when accessing HIV care services in Zimbabwe

Abstract: Key populations are disproportionately affected by human immunodeficiency virus (HIV) but under-represented in HIV testing and treatment programmes (World Health Organization [WHO] 2017:15). In spite of the fact that key populations constitute a small proportion of the general population globally, statistics indicate that in 2018, more than half (54%) of the new infections were from key populations and their partners (UNAIDS 2019a). To achieve HIV epidemic control, it is critical that key populations have acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…Similar initiatives may be considered for Zimbabwean SGM, given that avoidance of healthcare services and concealment of SGM status while seeking healthcare were two of the most commonly reported acts of stigma in our study. Similarly, findings from a qualitative study describing the experience of MSM accessing HIV services in Bulawayo, Zimbabwe indicated that MSM who disclosed their sexual orientation often experienced stigmatization by healthcare providers, leading to fear of seeking services [51]. While mitigating healthcare-related stigma is critical, as Mutanga and Moen describe in their 2019 qualitative analysis of sexuality-related stigma among gay and bisexual men in Zimbabwe, reducing stigma among SGMs in this context requires multifaceted interventions targeting stigma at the individual, community, and government levels [25].…”
Section: Discussionmentioning
confidence: 99%
“…Similar initiatives may be considered for Zimbabwean SGM, given that avoidance of healthcare services and concealment of SGM status while seeking healthcare were two of the most commonly reported acts of stigma in our study. Similarly, findings from a qualitative study describing the experience of MSM accessing HIV services in Bulawayo, Zimbabwe indicated that MSM who disclosed their sexual orientation often experienced stigmatization by healthcare providers, leading to fear of seeking services [51]. While mitigating healthcare-related stigma is critical, as Mutanga and Moen describe in their 2019 qualitative analysis of sexuality-related stigma among gay and bisexual men in Zimbabwe, reducing stigma among SGMs in this context requires multifaceted interventions targeting stigma at the individual, community, and government levels [25].…”
Section: Discussionmentioning
confidence: 99%
“…These numbers are alarming, hence the need for MSM to access sexual and reproductive health services (SRHS) because curbing the HIV epidemic cannot be possible without reaching this population ( Gupta & Granich, 2017 ). Accessing SRHS such as PrEP by MSM in Bulawayo is highly influenced by barriers such as discrimination, stigma and social exclusion ( Moyo et al, 2021 ), and the existence of public health care facilities that have no standardized services that cater for the needs of MSM ( Munyimani & Nunu, 2022 ). This research article aims to explore the accessibility of PrEP, knowledge of PrEP among MSM, potential barriers, and facilitators to improve PrEP uptake among this population.…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen articles13 68–80 were partially intersectional stigma studies incorporating an intersectional approach to some elements of the analysis or presentation of their findings. We also identified 10 articles81–90 that studied multiple stigmas in a non-intersectional manner and 142 articles4 13 16–18 21 51 52 91–224 that studied one stigma in one population of SGM or studied one stigma in each of multiple populations (eg, SSSAB stigma only among MSM and transgender stigma only among TGW). A summary of each intersectional stigma study (n=21) appears in online supplemental file 2 and a summary of each non-intersectional stigma study (n=152) appears in online supplemental file 3.…”
Section: Resultsmentioning
confidence: 99%